The study of dipole moment of some substituted acetic acids in an electronically excited state - Murthy, M (2003)
The electronic absorption spectra of eight substituted acetic acids have been measured at room temperature in several solvents. The ground state dipole moments are evaluated experimentally for these molecules. These ground state values are used in conjunction with the spectral results to evaluate their first electronically excited state dipole moments. For all the molecules investigated here the dipole moments in the excited state are higher than their ground state values. (C) 2002 Elsevier Science B.V. All rights reserved.